Identification of Virginia‐Type Peanut Genotypes for Water‐Deficit Conditions Based on Early Decrease in Transpiration Rate with Soil Drying. Issue 6 (4th October 2018) - Sinclair, Thomas R.; Shekoofa, Avat; Isleib, Thomas G.; Balota, Maria; Zhang, Hao
Abstract : Early decrease in transpiration rate as soil progressively dries allows soil water conservation for sustained crop physiological activity as water deficit continues to increase. This trait is likely to be particularly useful for peanut ( Arachis hypogaea L.), which is often grown on sandy soil where water deficit can develop quickly. This study was undertaken to identify peanut genotypes that express this water conservation trait and to determine if it confers a yield advantage. Three approaches were taken. (i) Two populations of peanut were tested in controlled environments during progressive soil drying. Especially high thresholds of soil water content for initiation of decrease in transpiration rate were identified in three lines in each of the breeding populations. (ii) Nine genotypes were identified for field observation of leaf wilting under rain shelters and in the open field. There was a correspondence between the early decrease in transpiration rate with soil drying and delayed wilting. (iii) Yield trial data for three genotypes were examined to identify those lines that consistently had higher yields than the commercial check cultivar 'Bailey', particularly at low yield levels commonly associated with drier conditions. When expressing total seed yield in monetary return, these breeding lines had yield values that were consistently superior to Bailey below the US$2000 ha −1 threshold. Based on the three experimental approaches, N12006ol consistently expressed a desired response of early decrease in transpiration rate with soil drying, delayed wilting in the field when soil water deficit developed, and greater yield value than Bailey in low‐yield environments.